Anthropometric measurements as a significant for choosing juniors in both volleyball and handball sports (factorial analysis study) - Nabieh Ibrahim Mohamed, A. (World Journal of Sport Sciences, 2010)
The research aims to identify the important anthropometry measurements,which represent the basic dimensions of the body in both sports, volleyball and handball,from Egyptian juniors in the age from 15 to 18 years, by moving from diversity and abundance which are represented in the original anthropometric included in the study to the few that are in clusters or common factors derived from the study for each sports the same search every individual and determine the number of anthropometry measurements under search - included in the analysis - to a smaller number depends on the amount of factors saturates joint derived from the analysis, which may provide researchers and trainers time and effort when trying to apply these anthropometry measurements for the selection of juniors and identifying the anthropometric factors associated with each sport, volleyball and handball, separately and the name of these factors and hypotheses of the research building factorial analysis of forty-four anthropometric measurements and identify the most important standard anthropometric factors in both volleyball and handball and find the statistical differences the function in the most important measurements anthropometric between volleyball and handball for volleyball. The researcher used the descriptive manner, the survey,as an appropriate method to achieve the objectives of the research, as the researcher used factorial analysis as a picture approach,descriptive,.The research sample included 61 juniors, divided into 25 juniors of volleyball and 36 for handball. Selecting the research sample was by using of of the method of random sample and included a sample of some Egyptian juniors in volleyball and handball, registered in Egyptian sports federations of the two sports.The researcher applied the 44 anthropometry variables under study on a pilot study, on the number of 30 juniors were selected from junior and outside the sample basic research and that was at 15 juniors of volleyball, 15 juniors of handball and be credited to the validity and reliability of the measurements of anthropometric, has made transactions stability elevated limited between 1 to 0.934,and all statistically significant at 0.01 level, which indicates the stability of measurements. The results of recycling factorial orthogonal for a class volleyball revealed the admission of five main factors, three factors expatriates, that the results of recycling factorial orthogonal to the category of handball revealed on the acceptance of three key factors, five factors other than pure, that the results of recycling factorial orthogonal to the category of volleyball revealed for the admission of five key factors are: along the lower limb, lengths and offers some parts of the body, circumference of upper limb, obesity of the upper part, of the lower limb and three factors expatriates, that the results of recycling factorial orthogonal to the category of Handball revealed on the acceptance of three key factors are the breadth, obesity and circumferences and five factors other than pure, there are significant differences in the abstract level 0.01 between both volleyball and handball from the results of anthropometric measurements, the values of "t" calculated ranged from -0.77 to -22.17, in light of the objectives of the research and the limits of the sample and on the basis to refer to the results and conclusions, the researcher recommends that the anthropometric measurements, resulted from the current study, are among the most important foundations which take into account when choosing players of volleyball and handball.